Hydrogen atom-ion synergy in surface lattice modification at sub-threshold energy. (December 2020) - Gao, L.; Wilde, M.; Manhard, A.; von Toussaint, U.; Jacob, W.
Abstract: Low-energy hydrogen-isotope (HI) plasma is widely applied for industrial surface processing. Here we demonstrate that HI plasma - even with ion energies far below the threshold for stable Frenkel pair production - can strongly modify crystalline materials by forming heavily lattice-distorted surface layers with a thickness of several nanometers and a HI content of several atomic percent. We experimentally reproduce the identical lattice modification at deuterium and hydrogen plasma-irradiated tungsten (W) surfaces when the sub-threshold HI ion energies are adjusted such as to transfer equal amounts of kinetic energy in collisions with W lattice atoms. A physical model for the low-energy generation of primary defects is proposed, which involves the synergy between temporary Frenkel pair creation by sub-threshold HI ion collisions and vacancy stabilization by trapping of solute HI atoms. Such synergistic defect generation is generally expected upon injection of energetic projectiles (ions, neutrons) into HI-containing solids and likely contributes to material degradation. As a means of surface modification, the fabrication of nanometer-scale hydrogen-rich surface layers on materials (even those with negligible hydrogen solubility) via low-energy H plasma exposure promises utilization potential in catalysis and electrochemistry. Graphical abstract: Image, graphical abstract